2021
DOI: 10.18632/aging.202411
|View full text |Cite
|
Sign up to set email alerts
|

Identification of therapeutic targets and prognostic biomarkers from the hnRNP family in invasive breast carcinoma

Abstract: Heterogeneous nuclear ribonucleoproteins (hnRNPs) are RNA-binding proteins that are reported to play a crucial role in the pathogenic process of multiple malignancies. However, their expression patterns, clinical application significance and prognostic values in invasive breast carcinoma (BRCA) remain unknown. In this study, we investigated hnRNP family members in BRCA using accumulated data from Oncomine 4.5, UALCAN Web portal and other available databases. We explored the expression and prognostic value leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It controls various cell functions such as transcription, nuclear chromatin organization, alternative pre-mRNA splicing, telomere-length regulation, inhibition of apoptosis, angiogenesis, or cell invasion [ 8 10 ]. Mounting evidence suggests that HNRNP family members play an essential role in numerous cancers, including breast cancer, ovarian cancer, hepatocellular cancer, melanoma, bladder cancer, prostate cancer and pancreatic cancer [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It controls various cell functions such as transcription, nuclear chromatin organization, alternative pre-mRNA splicing, telomere-length regulation, inhibition of apoptosis, angiogenesis, or cell invasion [ 8 10 ]. Mounting evidence suggests that HNRNP family members play an essential role in numerous cancers, including breast cancer, ovarian cancer, hepatocellular cancer, melanoma, bladder cancer, prostate cancer and pancreatic cancer [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, hnRNPU plays a critical role in regulating chromatin dynamics through functional interaction with cohesion complex and chromatin loop formation [ 32 , 33 ]. Dysregulation of hnRNPU results in carcinogenesis and drug resistance [ 34 , 35 , 42 ]. Co-immunoprecipitation assays performed in MDA-MB-468 cells confirmed the interaction between endogenous CDC20 and hnRNPU ( Figure 3 f).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, hnRNPU expression was associated with cisplatin sensitivity in bladder cancer [ 42 ]. Additionally, hnRNPU has been shown to promote breast cancer cell proliferation, migration, and invasion [ 35 ]. CTCF can also affect breast cancer development by regulating target genes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, calreticulin has been found to interact with several GPCR proteins such as AT1R and V2R 44 . Jiawei Zhou et al found HNRNPU enhances epithelial-mesenchymal transition, invasion capacity but represses the viability of invasive breast carcinoma cells 45 . Circadian gene clocks and their target genes are involved in a number of cell functions including proliferation, differentiation, metabolism, migration, and secretion 46-50 .…”
Section: Discussionmentioning
confidence: 99%